An echelon internal heating strategy for lithium-ion battery. (December 2017) - Guo, Shanshan; Xiong, Rui; Sun, Fengchun; Cao, Jiayi; Wang, Kan
Abstract: An echelon heating strategy to preheat lithium-ion battery internally at low temperatures with alternating current (AC) is developed. An electro-thermal coupled model is developed to achieve a good balance between rapid heat generation rate and less damage to battery lifetime. Using this model the optimal frequency for maximum heat generation rate at a certain ambient conditions is determined and experimentally validated. The optimal time to change the current amplitude during preheating is calculated at a certain temperature by the theoretical formula based on terminal voltage within the allowable range. Experimental results demonstrate that the heat generation rate at the optimal frequency and variable current amplitude is fast with high efﬁciency and no voltage overrun. The battery can be heated from -20°C to 10 °C within 905 seconds, and the average temperature-rise is 1.99°C/min. The proposed AC heating strategy is experimentally veriﬁed with no apparent damage to battery life and can be consulted for engineering to preheat batteries in electric vehicles.